Dielectric anisotropy, and diffraction efficiency properties of a doped nematic liquid crystal - Yakuphanoğlu, Fahrettin; Okutan, M.; Koysal, O.; Ahn, S.-M.; Keum, S. R. (Elsevier Sci Ltd, 2008)
The dielectric anisotropy and diffraction efficiency properties of E7 liquid crystal and SPCI-C7 doped liquid crystal composite have been investigated. The dielectric constant components (epsilon(parallel to) and epsilon(perpendicular to)) in the nematic phase of E7 were measured as a function of frequency. The liquid crystals exhibited dielectrically-control led positive dielectric anisotropy (p-type Delta epsilon) with transition to negative dielectric anisotropy (n-type Delta epsilon). SPCI-C7 doping lowered dielectric anisotropy and increased the diffraction efficiency of ET The refractive index modulation values of E7 and E7/SPCI-C7 were Delta n = 3.9 x 10(-3) and Delta n = 6.95 x 10(-3), respectively, and this parameter was increased by doping. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: liquid crystal; SPCI-C7; dielectric anisotropy